PENGARUH PENYIMPANAN TERHADAP SIFAT KIMIA DAN VIABILITAS BENIH AREN - N. MASHUD; DAVID ALLORERUNG (Jurnal Penelitian Tanaman Industri, 2001)
Effect of storage duration on physical and chemical characteristics and viability of seed in sugar palm Arenga pinnataEffect of storage on (he physical and chemical characteristics and viability of sugar palm seed was studied in (he Research Institute for Coconut and Other Palm, Manado from April 1997 lo March 1998. The seeds were collecled from (he palm of 15 year old from Kemelcmbuai village, Motoling sub district, Minahasa North Sulawesi. The seeds were sown in the glass house. The carbohydrate, lipid and protein were analyzed at the laboratory of Research Institute for Coconut and Other Palm, Manado. The experimcnl was designed as a randomized block arranged factorial ly. The irst factor was storage duration (0,2, 4, 6, 8, or 10 weeks). Results showed that unshclling affected germination rate but did not germinability. The seed stored for 2 - 4 weeks showed high gcrminability (71%). Unshclling and storing reduced carbohydrate and lipid, but not protein. Carbohydrate reduction occurred at two weeks storage, either in (he shelled or unshellcd seed. Reduclion of carbohydrate more rapidly in (he shelled seed stored for 2-4 weeks. Storage for 2 weeks resulted in the reduction of protein. From this study it was suggested that for high germination, Ihe seed should be stored for 4 weeks before sowing.